Unravelling the nexus of plant response to non-microbial biostimulants under stress conditions - Ciriello, Michele; Fusco, Giovanna Marta; Woodrow, Pasqualina; Carillo, Petronia; Rouphael, Youssef (Plant stress (Amsterdam), 2024)
•An overview on the physiological and molecular mechanisms of biostimulants application on horticultural and agronomic crops is given.•Application of protein hydrolysates, seaweed extracts, humic acids and silicon can boost tolerance to abiotic stresses.•A systematic molecular characterization of the different biostimulants becomes essential to develop a second generation of biostimulants.•The review article identifies several potential research to exploit the biostimulants benefits in agriculture. Contemporary challenges facing the agricultural sector have garnered the interest of all stakeholders on the novel toolset of biostimulants. These products could serve as pivotal actors in the forthcoming transition toward ever more essential sustainable production practices. Regardless of their type, biostimulants have the potential to enhance resource efficiency while concurrently fortifying plant resilience to adverse abiotic stress factors. Recent research advances have fundamentally focused on assessing quantifiable parameters, largely overlooking the numerous and intricate biochemical, cellular, and metabolic interactions between plants and biostimulants. It is consequently not surprising that, to date, the mechanisms of action and basic biochemical processes underlying biostimulants’ effects on plants remain enigmatic. Concerning non-microbial biostimulants, which are the subject of in-depth exploration in this review, their inherently diverse nature, comprising formulations containing a plethora of distinct bioactive molecules, significantly complicates the investigation of mechanisms implicated in their mode of action. It is for this reason that we have rather elected to meticulously examine the effects, particularly in suboptimal environments, of a) protein hydrolysates; b) algal extracts; c) humic acids; and d) silicon. The objective of this analysis is to gain a comprehensive understanding of how these substances operate within plants by interpreting both their genetic and metabolic impacts. Comprehensive understanding of these effects could substantially underpin the reliability of these agents and usher to the identification of ever more effective formulations.